E – prestasi pensyarah (lecturer performance evaluation system) - Ahmad Khaidir, Hamzah (2013)
At present every job done will be assessed. Performance evaluation system has always been the focus of academics to assess its efficiency in learning. Similarly, lecturers who teach in the polytechnic in Malaysia will be assessed. Along with the development of information technology progress, there are problems in the conventional system it is file-based systems can be overcome. At each assessment time lecturers do often have difficulty in managing the questions that will be given to students. In addition, the time frame for completion of the evaluation takes a long time and interferes with learning and teaching time students and lecturers. At present, the assessment carried out using specific forms provided by the faculty. Use of the form is too much difficult for lecturers to store and update data for a long period. Lecturers Performance Evaluation System 'e-prestasi pensyarah' is a system developed for the convenience of lecturers, students and heads of departments. This system is the idea of the existing system. The main goal of this project is to create an alternative system to the existing system while increasing the effectiveness of staff performance evaluation process Polytechnic Sultan Mizan Zainal Abidin. Lecturers Performance Evaluation System incorporates some of the latest technology using Macromedia Dreamweaver MX 2004, as a programming language PHP5 and MySQL 4.1.12 as the database. "System Development Life Cycle (SDLC)" was chosen as the methodology with contact diagram and data flow diagram as a methodology in the development of this system. The system is also combined with the convenience of a short message system where after completing an evaluation of the lecturer will receive a report of their assessment scores directly to their mobile phone by text message. In general, this system can help lecturers and administrators to manage documents in a systematic performance evaluation of lecturers. In addition, it can be used to assess the performance of the particular academic staff work throughout the year.